Electrochemical Mechanism of Ferrocene-Based Redox Molecules in Thin Film Membrane Electrodes. (1st June 2017) - Cuartero, Maria; Acres, Robert G.; Bradley, John; Jarolimova, Zdenka; Wang, Lu; Bakker, Eric; Crespo, Gaston A.; De Marco, Roland
Graphical abstract: Cartoon illustrating NaCl permeation through water nanodroplets and Cl − exchange at the membrane/sample interface, both of which create an environment to enable the formation of FeCln 3−n complexes, leading to a non-reversibility in the redox chemistry of the membrane. Highlights: electrochemistry of ferrocene derivatives in polymeric membranes. role of chloride on the irreversible oxidation of ferrocene in thin film membranes. synchrotron radiation study of chloride on the ferrocene reactivity in membranes. elimination of chloride induced irreversibility of the ferrocene reaction chemistry. Abstract: Cyclic voltammetry (CV) in chloride-based aqueous electrolytes of ferrocene molecule doped thin membranes (∼200 nm in thickness) on glassy carbon (GC) substrate electrodes, both plasticized poly(vinyl chloride) (PVC) and unplasticized poly(methyl methacrylate)/poly(decyl methacrylate) (PMMA-PDMA) membranes, has shown that the electrochemical oxidation behavior is irreversible due most likely to degradation of ferrocene at the buried interface (GC|membrane). Furthermore, CV of the ferrocene molecules at GC electrodes in organic solvents employing chloride-based and chloride-free organic electrolytes has demonstrated that the chloride anion is inextricably linked to this irreversible ferrocene oxidation electrochemistry. Accordingly, we have explored the electrochemical oxidation mechanism of ferrocene-based redox molecules in thin film plasticized and unplasticized polymeric membrane electrodes by coupling synchrotron radiation-X-ray photoelectron spectroscopy (SR-XPS) and near edge X-ray absorption fine structure (NEXAFS) with argon ion sputtering to depth profile the electrochemically oxidized thin membrane systems. With the PVC depth profiling studies, it was not possible to precisely study the influence of chloride on the ferrocene reactivity due to the high atomic ratio of chloride in the PVC membrane; however, the depth profiling results obtained with a chlorine-free polymer (PMMA-PDMA) provided irrefutable evidence for the formation of a chloride-based iron product at the GC|PMMA-PDMA interface. Finally, we have identified conditions that prevent the irreversible conversion of ferrocene by utilizing a high loading of redox active reagent and/or an ionic liquid (IL) membrane plasticizer with high ionicity that suppresses the mass transfer of chloride.